REVIEW AND ESTABLISHING FRAMEWORK MODEL TO ADOPTION ISO 50001 ENERGY MANAGEMENT SYSTEM IN POWER STATIONS - Kamat, Seri Rahayu; Mahmood, Noor Shakir; Ajmi, Ahmed Ali (Journal of Advanced Manufacturing Technology (JAMT), 2016)
The energy sources around the world become scarce with increase prices. Governments and companies seek to develop technologies for energy management including ISO 50001. In nowadays, the reduce of the consumption electricity and the increase in energy efficiency have become is very important. To achieve these criteria, the organizations began to adoption ISO 50001 in every operational and organizational structure. ISO 50001 assist the large and small organizations to achieve the highest of the efficiency of the energy produced and an increase in the stability of organizations in private or public sectors. The ISO 50001 able to establish and create the framework model for any organization to improve the full energy management. This paper seeks to identify the most important variables in ISO 50001 that affect energy management in any power station. To increase the performance and efficiency of Power Stations. This paper presents a systematic review of the literature that has relation with adoption ISO 50001 in the power stations. This paper established a new conceptual framework for adoption ISO 50001 and to present the ISO 50001 as a system to energy management and increase the efficiency of the energy of organization in various fields. This study assumed to establish the framework model to test the performance of energy through ISO 50001 to include a set of factors that affect on the efficiency of energy in power stations like (Sustainability of Economic, Improvement the Quality, Performance of Environmental, Reduce of the costs and reduction of energy). The framework model that proposed in this paper supports the power stations by various methods to create energy sustainable in the power stations.